Adnominal demonstrative pronouns in North Saami youth radio programmes - Guttorm, Outi (Puhe ja kieli, 2019)
This article discusses the endophoric use of the adnominal demonstrative pronouns, especially dát ’this’ and diet ’it, the one near you’, in North Saami spoken by young adults. The aim is to show how demonstrative pronouns are used, and to what they refer in youth radio conversation, a setting in which referring to specific visible referents is not the first priority. In addition, the differences between pronouns as well as their functions will also be discussed. The data used in the study has been collected from Saami youth programmes aired on the Norwegian Broadcasting Company, NRK. In these programmes, the following demonstratives: dat ’that, it’, diet ‘it, the one near you’ and dát ‘this’ occur as endophoric pronouns, while the most common anaphoric pronoun is dat. In radio conversations, diet refers specifically to something that has been previously heard. It also refers to a referent which appears in another context, or to a subject introduced by one of the participants. The pronoun dát, on the other hand, brings the referent into particular focus, as well as being the most common cataphoric pronoun. The study reinforces and refines our earlier understanding of the use and meaning of the North Saami demonstrative pronouns. Tarkastelen tässä artikkelissa pohjoissaamen demonstratiivipronominien, erityisesti adnominaalisten pronominien dát ’tämä’ ja diet ’se (siinä)’ endoforista käyttöä nuorten puhekielessä. Tarkoituksenani on selvittää miten pronomineja käytetään ja mihin niillä viitataan nuorten radiokeskusteluissa, joissa viittaaminen näköpiirissä oleviin konkreettisiin tarkoitteisiin ei ole ensisijaista. Pohdin myös pronominien keskinäisiä eroja ja tehtäviä keskustelussa. Tutkimusaineisto on Norjan yleisradioyhtiö NRK:n saamenkielisistä nuortenohjelmista. Siinä endoforisina pronomineina esiintyvät dat ’se’, diet ’se (siinä) ja dát ’tämä’. Selkeästi yleisin anaforinen pronomini on dat. Radiokeskusteluissa diet-pronominilla viitataan erityisesti johonkin, josta on edellä kuultu. Sillä viitataan myös ...